A novel framework for identifying the interactions between biophysical and social components of an agricultural system: a guide for improving wheat production in Haryana, NW India. Issue 3 (27th May 2018) - Coventry, D. R.; Poswal, R. S.; Yadav, Ashok; Zhou, Yi; Riar, Amritbir; Kumar, Anuj; Sharma, R. K.; Chhokar, R. S.; Gupta, R. K.; Mehta, A. K.; Chand, Ramesh; Denton, M. D.; et al.
ABSTRACT: Purpose: The purpose of this study is to develop a conceptual framework with related analysis methodologies that identifies the influence of social environment on an established cropping system. Design/methodology/approach: A stratified survey including 103 villages and 823 farmers was conducted in all districts of Haryana (India). Firstly, technical efficiency (TE) was modeled using biophysical data including grain yield, seeding rate, wheat varieties, tillage, sowing date, seed source, harvesting method and the application of fertilizer, herbicide and irrigation. The relationship between TE and social community factors such as farm size, farmer age, level of education and agricultural support programs was analyzed by regression tree. Findings: TE was lower with the farmers who only have education to a primary standard. Farmers with high TE scores were mostly between 35 and 40 years of age, and a higher TE association was common for farmers who use technical publications. Social individual factors such as farmers' views on the future of farming were also analyzed across different TE levels. Practical implications: Farmers with lower TE are an obvious target for production improvement, particularly given the understanding that the overall production yield gap is small in Haryana. Theoretical implications: Our conceptual framework shows a quantitative way to establish the socio-ecological linkage, and to identify the opportunities for changes in management with extension services leading to productivity improvement. Originality/value: This paper provides a novel framework with detailed methodology to effectively identify the socio-economic factors that limit the biophysical production in an agricultural system.